Microstructure, oxidation behavior and adhesion of a CoNiCrAlTaY coating deposited on a high Nb–TiAl alloy by plasma surface metallizing technique. (September 2020) - Zheng, K.; Wang, Y.R.; Wang, R.Y.; Wang, Y.L.; Cheng, F.; Ma, Y.; Hei, H.J.; Gao, J.; Zhou, B.; Wang, Y.S.; Liang, Y.F.; Yu, S.W.; et al.
Abstract: A CoNiCrAlTaY coating was deposited on the Ti–45Al-8.5Nb substrate by plasma surface metallizing technique. The microstructure, morphology and composition of CoNiCrAlTaY-coated specimens were studied by X-ray diffractometer, scanning electron microscope, and transmission electron microscopy. The as-prepared coating consisted of mixed phases including Al13 Co4, CrCo, and Ni3 Al, resulting in an increased microhardness. The Al2 O3, CoO and Cr2 O3 phases formed during initial oxidation at 900 °C. However, Al2 O3 accompanied with CoCr2 O4, NiCr2 O4 and Cr2 TiO5 phases generated during isothermal oxidation, which was responsible for the oxidation resistance. These oxides leaded to the increased surface hardness of the coated specimens. The adhesion strength between the CoNiCrAlTaY coating and Ti–45Al-8.5Nb substrate were improved caused by the interdiffusion of involved elements. Highlights: A CoNiCrAlTaY coating was prepared on a Ti–45Al-8.5Nb alloy by plasma surface alloying technique. A CoNiCrAlTaY coating consisted of a deposited layer and a diffused layer. The generated oxides played a key in improving the oxidation resistance and microhardness. Gradient distribution of elements in the diffusion zone leaded to the high adhesion force between the coating and substrate.